2003
DOI: 10.1086/375536
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Bivalent Group B Streptococcal Conjugate Vaccine for Serotypes II and III

Abstract: To determine whether 2 monovalent group B streptococcus (GBS) serotype II or III capsular polysaccharide (CPS)-tetanus toxoid (TT) conjugate vaccines combined in a single intramuscular dose would elicit immune responses comparable to those of monovalent vaccines, 75 healthy adults were randomized to receive GBS II-TT (3.6 micro g of CPS), GBS III-TT (12.5 micro g of CPS), or a bivalent mixture of GBS II-TT/III-TT vaccine (double-masked design). Vaccines were well tolerated. Four-fold or greater increases in GB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 29 publications
1
50
0
2
Order By: Relevance
“…Antisera from multivalent vaccination groups could also block receptor binding of evolutionarily distinct GI.1 (NV genocluster) and GII.4 (LV genocluster) VLPs (30; also data not shown), suggesting that blockade responses may be genocluster rather than strain specific and may be of particular importance when applied to the GII.4 norovirus vaccine design. Previous studies of multivalent vaccination to Neisseria and Streptococcus species induced cross-reactive antibodies that could neutralize heterologous serotypes (2,22); however, multivalent HIV envelope vaccines failed to induce cross-reactive neutralizing antibody responses (10). Together, these data support the rationale for including multiple norovirus strains from different genogroups in a comprehensive norovirus vaccine.…”
Section: Discussionsupporting
confidence: 52%
“…Antisera from multivalent vaccination groups could also block receptor binding of evolutionarily distinct GI.1 (NV genocluster) and GII.4 (LV genocluster) VLPs (30; also data not shown), suggesting that blockade responses may be genocluster rather than strain specific and may be of particular importance when applied to the GII.4 norovirus vaccine design. Previous studies of multivalent vaccination to Neisseria and Streptococcus species induced cross-reactive antibodies that could neutralize heterologous serotypes (2,22); however, multivalent HIV envelope vaccines failed to induce cross-reactive neutralizing antibody responses (10). Together, these data support the rationale for including multiple norovirus strains from different genogroups in a comprehensive norovirus vaccine.…”
Section: Discussionsupporting
confidence: 52%
“…En los últimos años se han evaluado vacunas en mujeres no embarazadas, que contienen antí-genos capsulares de los serotipos Ia y Ib ó II y III (en forma individual o en combinación), conjugados con toxoide tetánico, con buena capacidad inmunogénica en ensayos de fagocitosis in vitro 17,18 . Recientemente se evaluó una vacuna conjugada conteniendo polisacárido capsular del serotipo III en embarazadas de 30 a 32 semanas de gestación, siendo bien tolerada por las madres y sus hijos 29 .…”
Section: N V E S T I G a C I ó Nunclassified
“…La vigilancia epidemiológica de la distribución de serotipos es importante para el desarrollo y elección de vacunas conjugadas, actualmente en evaluación 17,18 .…”
unclassified
“…However, studies carried out in the 1990s showed that conjugation of the polysaccharide to various protein carriers led to the stimulation of T-cell-dependent antigenic recognition and profound enhancement of the immunogenicity of CPS vaccines (5,6,60,61) An alternative strategy for protection against GBS infection would be to develop a vaccine with a conserved surface protein antigen. Surface antigens represent good candidates for vaccines, as antibodies directed against these targets have the potential to interfere with bacterial virulence and also to promote opsonophagocytosis through binding to ␥Fc receptors on phagocytes (17,44).…”
mentioning
confidence: 99%